Molecular Mechanism of β-Sitosterol and its Derivatives in Tumor Progression - Bao, Xingxun; Zhang, Yanan; Zhang, Hairong; Xia, Lei (Frontiers in Oncology, 2022)
β-Sitosterol (SIT), a white powdery organic substance with a molecular formula of C29H50O, is a natural compound that exists in plants such as different fruits and nuts and is also one of the most abundant phytosterols. With a chemical composition similar to that of cholesterol, SIT is applied in fields such as medicine, agriculture and the chemical industry owing, to its unique biological and physicochemical properties. Modern pharmacological studies have elucidated a good anti-tumor medicinal effect of SIT, which mainly manifests as pro-apoptotic, anti-proliferative, anti-metastatic, anti-invasive, and chemosensitizing effects on tumor cells. In addition, SIT exerts an anti-tumor effect on multiple malignant tumors such as breast, gastric, lung, kidney, pancreatic, prostate, and other cancers. This article reviews studies relevant to the anti-tumor effects of SIT in recent years and summarizes its anti-tumor mechanism to provide a reference for the clinical treatment of malignant tumors and the development of novel anti-tumor drugs.